Deterioro por corrosión de elementos de concreto armado de un edificio industrial - San Miguel, G. F.; Tamez, P. V.; Alvarado, M. R.; Alcorta, R. G.; Garza, R. M.; Farias, J. P. (Revista ALCONPAT, 2012)
Corrosion of reinforced concrete structures (RCS) is accentuated when there are placed in environments with extremely aggressive microclimates. In many parts of the world, the ability to evaluate the corrosion of rebars in these RCS and estimate the remaining service life is subject of study. This work shows that the implementation of an inspection and diagnosis methodology must generate reliable data, through the use of specialized equipment and technology. Additionally, the development of planning processes in rehabilitation interventions and/or maintenance of reinforced concrete elements should be privileged. The results obtained allowed the optimization of human and material resources of the end user. Keywords: corrosion; reinforced concrete; evaluation; rehabilitation.